Anionic Complexes of Nickel(II) and Copper(II) Containing Uni-negative Bidentate Ligands - Minati Satpathy, Ms.; Pradhan, B. (Asian Journal of Chemistry, 2010)
A series of complexes of the type [M´ (BB´)] where M´ = Me4N+, Cepy+, M = Ni(II) or Cu(II); BB´ = uni-negative bidentate ligands such as acetylacetone, pyridine carboxylic acid, oxine and diethylditho-carbamate have been prepared. The nature of bonding and the possible structures of the complexes are discussed. When provided with such an anionic environment. Ni(II) and Cu(II) were found to stabilise octahedral stereochemistry.